Management and outcome of anastomotic leakage after colonic surgery - Rickert, Alexander Lothar; Willeke, Frank; Kienle, Peter; Post, Stefan (Colorectal disease, 2010)
Aim Anastomotic leakage remains a key factor for morbidity after colonic surgery. The aim of the study was to analyse the outcome of different therapeutical approaches. Method Of 1731 consecutive patients undergoing colonic resection between 1998 and 2005 at our institution, 67 patients with anastomotic leakage were identified from a prospective database. A logistic regression model was used to determine factors which influenced the therapeutic approach and outcome. Results The overall anastomotic leakage rate was 3.5%. All patients were re-operated. The anastomosis was resected without restoration of continuity in 31 but preserved in 36 patients. An ileostomy was constructed in 27 of 36 patients with anastomotic leakage after repair or revision of the anastomosis, the remaining nine cases were treated without ileostomy. Five of these latter nine vs three of the 27 patients with ileostomy experienced re-leakage (P = 0.05). The overall mortality was 25%. The Mannheim Peritonitis Index was 17.44 for survivors vs 25.64 for nonsurvivors (P < 0.001). Restoration of intestinal continuity was performed in 95% of the patients with ileostomy and in 88% after Hartmann’s procedure. Multivariate analysis identified multi organ failure as the only factor predictive of a fatal outcome (P < 0.001). An ASA-score of more than 2 (P = 0.02) and peritonitis (P = 0.002) were reasons for not preserving the anastomosis. Conclusion Repair or redo of the anastomosis without a protective ileostomy frequently results in failure of the procedure. After Hartmann’s operation or split stoma creation a majority of patients undergo restoration of intestinal continuity.
Zuerst veröffentlicht 11. Dezember 2009
Gesehen am 15.05.2023